The Importance Role of Employees in Responding Crisis Communication - Dewi Risanti, Yuliani; El Karimah , Kismiyati; Nurhayati, Masayu (International Journal of Psychosocial Rehabilitation, 2020)
Past research shows that reputation and image is very important to the continuity and sustainability of the organizations. Recently, it can be easily damaged by the uncontrolled message circulation that spread on social media. Consumers tend to mislead by untrusted source of information causing losing their trust and give immediate impact to sales decline. One of the vulnerable company that regularly facing this situation is food and beverage industry. Garudafood that known for their peanuts products as the object of this case study has to deal with the negative issues about their company which spread on social media that goes viral within second causing crisis. In order to tackle the issues, commonly organizations held press conference and carefully appointed who will be the spokesperson to talk to mass media and wishing media will spread clarification messages correctly. As crisis become a more frequent occurrence, Garudafood applied different approach in handling the situation. This study aims to examine the importance role of employee as internal stakeholders of the company in responding negative issues that can lead to crisis. In how crisis communications plan is done by utilizing employees as source of information to external stakeholders in particular customers. Data collections through depth interview with the representative of corporate communications and relations of the company supported by literature and previous research. Results shows employees are able to be an essential role in responding crisis communications since they can be as source of information on behalf of the company to their relatives, friends and communities. However, their credibility is being considered since they have interest therefore tend to defend their workplace. After all, the company should release official clarification message that supported with the statement of related parties to increase the credibility of the message and source of information.